COMPARISON IMMUNOHISTOCHEMISTRY EXPRESSION OF DESIDUAL NATURAL KILLER (dNK) IN SEVERE PREECLAMPSIAAND NORMAL PREGNANCY - LUBIS, MUARA P. (International Journal of Current Pharmaceutical Research, 2020)
Objective: Preeclampsia characterized systematically by extensive vascular endothelial dysfunction and microangiopathy on mother, dNK is very important for the success of placentation. They are the key mediator of maternal immune system interactions with fetal cells. dNK cells are also involved in the modulation of EVT and the remodeling of spiral arteries. Methods: Analytic research with cross-sectional study, with samples of pregnant women who suffer from severe PE and aterm pregnancy which came to H. Adam Malik Hospital and Networking Hospital, November 2015-April 2016. The samples are 46 women, who met the inclusion criteria. Results: Immunohistochemistry examination dNK cell in the severe PE case group and control group, statistically found p<0,05. dNK placenta expression in the severe preeclampsia case group gives an overview of expression with a mean of 2.55±2.31, while the control group of normal pregnancy had higher mean is 8.66±3.16. Conclusion: The examination of immunohistochemistry of dNK cells showed there is a significant difference in the expression of Immuno-histochemistry dNK cells between severe PE case group and non severe PE.